Chemical Topology and Complexity of Protein Architectures. Issue 10 (October 2018) - Wang, Xiao-Wei; Zhang, Wen-Bin
Abstract : Chemical topology has emerged as one intriguing feature in protein engineering. Nature demonstrates the elegance and power of protein topology engineering in the unique biofunctions and exceptional stabilities of cyclotides and lasso peptides. With entangling protein motifs and genetically encoded peptide–protein chemistry, artificial proteins with complex topologies, including cyclic proteins, star proteins, and protein catenanes, have become accessible. Among them, proteins with mechanical bonds ('mechanoproteins') are of special interest, owing to their potential functional benefits such as structure stabilization, quaternary structure control, synergistic multivalency effect, and dynamic mechanical sliding/switching properties. In this review article, we summarize recent progress in the field of protein topology engineering as well as the challenges and opportunities that it holds. Highlights: Chemical topology of the protein backbone has become an important dimension in protein engineering for tuning the stability and dynamic properties of proteins. Natural proteins with nonlinear backbones or nontrivial topologies exist largely in places where exceptional stability is desired. Mechanoproteins are proteins containing one or more mechanical bonds. The dynamic nature of mechanical bonds in proteins has been demonstrated in lasso peptides exhibiting thermally switchable properties. As a powerful toolset, genetically encoded peptide–protein chemistry has facilitated the design and synthesis of artificial proteins with complex topologies including cyclic, branched, tadpole, lasso, rotaxane, and catenane architectures.